The Effect of School Voucher Spending on Initial Earnings - Juan A. Correa; Francisco Parro; Rafael Sánchez (Institute of Labor Economics (IZA), 2021)
We quantify the effect of school voucher spending on initial earnings. We use administrative data on the monetary resources received by schools from a targeted voucher program implemented in Chile. We merge this dataset with education and labor market administrative records for the universe of students enrolled in the Chilean education system. We find that an increase of US100 in the yearly expenditure of voucher resources per student raises initial earnings by 2.3%. However, we find that the positive effect of voucher spending only holds for private voucher schools that operate in local education markets with low enrollment concentration.
Keywords: H52; I22; I26; I28; 330; school vouchers; education spending; earnings